Patriotism as a Factor of Civic Identification and National Unity - A. I. Kugay (Управленческое консультирование, 2018)
The instrument of pressure on Russia is not only a sanctions policy, but also a policy aimed at depersonalizing national consciousness, stimulating discrediting and disavowing the notion of patriotism in different segments of society. The article considers the nature and typology of patriotism, its existential, political, historical, mythological and religious grounds. State and civil patriotism, as love for the «great Motherland», is largely a constructed phenomenon — the fruit of the efforts of the elite, social institutions to ensure national unity. Otherwise, the people lost their national consciousness, lost their spiritual and socio-cultural guidelines, adopted a new system of values, transformed into another people, or become a «population», losing their former identity without finding a new one. Went «mad», wanted to come back, and there is already another. Busy tone!